Differences by sex and type of hypertension in mortality from hypertensive diseases between 1997 and 2020, and predictions for 2035 in Latin American and Caribbean countries - J. Smith Torres-Roman; Romina Barrera-Quispe; Carlos Quispe-Vicuña; Wagner Rios-Garcia; Bryan Rudas-Sulca; Yenko Damjanovic-Burga; Ivan Alegre-Cordero; Carito Zumaeta-Cabrera; Abdier Vizcarra-Tellez; Luis M. Tasayco-Márquez; Milward Ubillus; Carlo La Vecchia (PLoS ONE, 2026)
Background Hypertension is the most prevalent cardiovascular condition and a leading contributor to premature mortality in Latin America and the Caribbean (LAC). Despite its public health relevance, few studies have examined long-term trends in hypertensive disease mortality across the region. The objective was to analyze trends in mortality due to hypertensive diseases from 1997 to 2020 in LAC countries, disaggregated by sex and type of hypertension, and to project mortality rates to 2035. Methods We conducted an ecological time-series study using age-standardized mortality rates (ASMRs) extracted from the World Health Organization Mortality Database. Mortality from hypertensive diseases was defined by ICD-10 codes I10–I13 and further stratified into primary hypertension (I10) and hypertension-mediated organ damage (HMOD, I11–I13). Trends were assessed using Joinpoint regression to estimate average annual percent change (AAPC) and 95% confidence intervals (95%CI). Projections to 2035 were calculated using Norpred based on age – period – cohort analysis. Results Between 1997 and 2020, mortality from hypertensive diseases increased in most LAC countries. Among men, significant increases were observed in Brazil (AAPC: 2.6%), El Salvador (6.6%), and Panama (6.1%), while Trinidad and Tobago was the only country showing a significant decline (AAPC: −5.7%). Among women, the most marked increase was seen in El Salvador (7.6%). By 2035, the Dominican Republic, Venezuela, and Paraguay are projected to have the highest ASMRs for hypertensive diseases among men, while for women, the Dominican Republic and Venezuela will remain among the most affected. Mortality from primary hypertension represented the greatest burden across countries, while HMOD exhibited lower but variable rates. Conclusion Hypertensive disease mortality is projected to rise in LAC, with notable disparities by sex, country, and type of hypertension. These findings underscore the urgent need for regionally tailored prevention, screening, and control strategies.